Bus rapid transit arrives in Barranquilla, Colombia: Understanding a changing landscape through residents' travel experiences. (October 2020) - Santana Palacios, Manuel; Cochran, Abigail; Bell, Corwin; Hernández Jiménez, Ulises; Leshner, Eleanor; Trejo Morales, Francisco; Chatman, Daniel G.
Highlights: We describe how the travel experiences of residents of Barranquilla, Colombia have changed since a BRT was deployed. Interviewees expressed mixed feelings about the transition. Our findings raise questions about equity and system legibility that emerged with BRT implementation. We identified a divide in expectations about the BRT between residents and planners. Interviews revealed a complex interaction among private transport services and the BRT. Abstract: In this article, we describe how the travel experiences of residents of Barranquilla, Colombia have changed since a new bus rapid transit system was deployed in 2010 along with changes to pre-existing private transit services. We recruited interview participants using intercept methods at more than fifteen locations, conducted dozens of semi-structured interviews, and used collaborative and iterative coding to analyze the data. Interviewees expressed mixed feelings about the transition from private transit to the hybrid BRT-private transit system. Many were pleased about reductions in travel time, the air conditioning on BRT vehicles, and an increased sense of safety from crime. But most interviewees also identified significant drawbacks, most notably overcrowding, the insufficiency and complexity of BRT feeder routes, and the elimination of several private transit bus routes. While the free transfer between BRT trunk and feeder routes reduced some users' out-of-pocket costs, some interviewees, expressed disappointment at losing the ability to bargain over fares. Our findings raise questions about equity in access and affordability, as well as issues of system legibility that emerged with BRT implementation. Another critical lesson from our research points out to a potentially significant problem: while BRT planners tended to focus on safety improvements and mitigating environmental damage, such goals seem to have come at the expense of other aspects that users see as more important, such as reducing improving travel times. Finally, our interviews revealed a complex interaction among transport services, in which some private transit lines complement BRT services while others compete with them.